Efficient Low Threshold Frequency Conversion in AlGaAs-On-Insulator Waveguides - Ulsig, Emil Z.; Degli-Eredi, Iterio; Stanton, Eric J.; Volet, Nicolas (Frontiers in Photonics, 2022)
A design study is presented for an efficient, compact and robust device to convert the frequency of single-photons from the near-infrared to the telecom C-band. The material platform aluminum gallium arsenide (AlGaAs)-on-insulator, with its relatively large second-order nonlinearity, is used to create highly confined optical modes. This platform can feasibly incorporate single-photon emitters such as indium arsenide (InAs) on gallium arsenide (GaAs), paving the way towards direct integration of single-photon sources and nonlinear waveguides on the same chip. In this design study, single-pass difference-frequency generation (DFG) producing C-band single-photons is enabled via form birefringent phase-matching between a 930 nm single-photon pump and continuous wave (CW) idler at 2325 nm. In particular the idler and single-photons are combined with an on-chip directional coupler, and then tapered to a single waveguide where the three modes are phase-matched. The design is studied at a special case, showing high fabrication tolerances, and an internal conversion efficiency up to 41%.